Peran Komunikasi Guru dalam Menumbuhkan Motivasi Belajar Siswa di Tingkat Sekolah Dasar/Madrasah Ibtidaiyah - Suparlan, Suparlan (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2022)
Communication is the process of sending or receiving messages from one person, either directly or indirectly, in written, spoken, nonverbal language. The person who communicates is called the communicator. The person who is invited to communicate is called the communicant. People who are able to communicate effectively are called communicatives. A communicative person is a person who is able to convey information or messages to others, either directly or indirectly, verbally, or in nonverbal language so that other people can receive information (messages) in accordance with the expectations of the informant (messages). Learning as a process of adjustment or adjustment of behavior that runs progressively. Meanwhile, Morgan defines learning as a relatively permanent change in behavior as a result or result of a disturbing experience.